Moderate Islam vis-a-vis Salafism in Indonesia: An Ideological Competition - Denny Febriansyah; Dawoud Sudqi el-Alami (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
A unique moderate style of Islam in Indonesia was believed to be the first entrance of Islam to the Indonesian archipelago. This model adopted a moderate approach of spreading Islam, not fundamental nor radical. The oil boom of Saudi Arabia in the 1970s promoted the spreading of Salafism in Indonesia. This group, known as Wahhabism, started to flourish from the 1970s until now. This study examines the contestation of moderate Islamic movement vis a vis Salafism in Indonesia from the 1970s to 2018. The data in this study were collected from any related literature such as books, articles, and internet sources. All information was presented by using a method of formal library research. This study reveals that the competition between these two groups has been taking place since the 1970s. With the massive attack from the Salafism group, the Moderate Islamic movement responded by introducing ‘Islam Nusantara’ (Islam that accommodates customs and cultures in the Indonesian archipelago) to strengthen the moderate style of Islam in Indonesia. The response of the Moderate Islamic movement includes many aspects, such as through the educational sector and establishing mass Islamic organizations.